Carbon balance in steppe and forest-steppe agroecosystems of Altai Territory - B. A. Krasnoyarova; A. E. Nazarenko; T. G. Plutalova; S. N. Sharabarina (Юг России: экология, развитие, 2025)
Carbon balance assessment of farms in various natural conditions within the boundaries of the Altai Territory in order to reduce carbon emissions. The study covers 4 farms, more than 30 thousand hectares of arable land and 13 agricultural crops. The methodological basis for the assessments is the methodology for determining the volumes of emissions and absorption of greenhouse gases approved by the Ministry of Natural Resources of the Russian Federation in 2022.On each farm, the soil under different crops has a unique carbon balance and therefore the choice of crops grown and their cultivation technologies determines the carbon balance of the farm. The maximum contribution to carbon accumulation comes from the entry of plant residues into the soil; the application of mineral fertilizers also plays an important role. The main components of carbon emissions are its losses through haymaking, erosion and deflation. Soil respiration takes up a small share in the overall carbon balance.In the dry steppe zone, a negative carbon balance was revealed for all types of crops studied, except for spring wheat. In the forest‐steppe zone, carbon accumulation was noted for wheat, rapeseed and barley, and losses were noted for buckwheat and peas. In the foothill steppe zone, an increase in carbon in the soil is also typical for wheat, barley and sunflower, while a decrease is typical for buckwheat, soybeans, rapeseed, alfalfa and haylage. The greatest carbon losses occur in fields occupied by forage crops, which is associated with the removal of plant residues during harvesting.